Algebraic reasoning of high school students in solving inverse function problems: Viewed from mathematical resilience - Fitrianna, Aflich Yusnita; Rosjanuardi, Rizky; Prabawanto, Sufyani (Universitas Islam Negeri Raden Intan Lampung, 2024)
Algebra is one of the essential branches of mathematics that often presents challenges for students, especially when faced with inverse function problems. This study aims to describe algebraic reasoning in solving inverse function problems from the perspective of students' mathematical resilience. This qualitative research uses a case study design involving 33 eleventh-grade students from a public high school in West Bandung Regency. The instruments used were a mathematical resilience scale and an algebraic reasoning test. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results showed that 15.15% of students had low resilience, 72.72% had moderate resilience, and 12.12% had high resilience. There were different characteristics in algebraic reasoning among students in these resilience categories. The implications indicate that targeted learning strategies can enhance algebraic reasoning, especially for moderate and low-resilience students.